Changes in kidney function among men having sex with men starting on demand tenofovir disoproxil fumarate – emtricitabine for HIV pre‐exposure prophylaxis. Issue 2 (22nd February 2020) - Liegeon, Geoffroy; Antoni, Guillemette; Pialoux, Gilles; Capitant, Catherine; Cotte, Laurent; Charreau, Isabelle; Tremblay, Cécile; Cua, Eric; Senneville, Eric; Raffi, François; Meyer, Laurence; Molina, Jean‐Michel; et al.
Abstract: Introduction: Daily pre‐exposure prophylaxis (PrEP) with tenofovir disoproxil fumarate/emtricitabine (TDF/FTC) is associated with a small but statistically significant decrease in estimated glomerular filtration rate (eGFR). We assessed the renal safety of on‐demand PrEP with TDF/FTC in HIV‐1 uninfected men. Methods: We used data from the randomized double‐blind placebo‐controlled ANRS‐IPERGAY trial and its open‐label extension conducted between February 2012 and June 2016 among HIV‐uninfected MSM starting on‐demand PrEP. Using linear mixed model, we evaluated the mean eGFR decline from baseline over time and determined risks factors associated with eGFR decline during the study. Results: During the blind phase, with a median follow‐up of 9.4 months, the mean decline slope of eGFR from baseline was −0.88 and −1.53 mL/min/1.73 m 2 per year in the placebo (n = 201) and the TDF/FTC group (n = 198) respectively, with a slope difference of 0.65 mL/min/1.73 m 2 per year ( p = 0.27). Including both phases, 389 participants started on‐demand TDF/FTC with a median follow‐up of 19.2 months and a mean decline of eGFR from baseline of −1.14 mL/min/1.73 m 2 per year ( p < 0.001). The slope of eGFR reduction was not significantly different in participants with baseline eGFR ≤ 90 mL/min/1.73 m 2 ( p = 0.44), age >40 years ( p = 0.24) or hypertension ( p = 0.21). There was a dose‐response relationship between recent tenofovir exposure and lower eGFR when considering the number of pills taken in the two months prior the visit (eGFR difference of −0.88 mL/min/1.73 m 2 between >15 pills/month vs. ≤15 pills/month, p < 0.01) or plasma tenofovir concentrations at the visit (eGFR difference compared to ≤2 ng/mL: >2 to ≤10ng/mL: −0.98 mL/min/1.73 m 2, >10 to ≤40ng/mL: −1.28 mL/min/1.73 m 2, >40 ng/mL: −1.82 mL/min/1.73 m 2, p < 0.001). Three participants discontinued TDF/FTC for eGFR < 60 mL/min/1.73 m 2 during the OLE phase. No case of Fanconi syndrome was reported. Conclusions: The renal safety of on‐demand PrEP with TDF/FTC was good. The overall reduction and intermittent exposure to TDF/FTC may explain this good renal safety.